Cryptoporus volvatus extract inhibits influenza virus replication in vitro and in vivo. - Li Gao; Yipeng Sun; Jianyong Si; Jinhua Liu; Guibo Sun; Xiaobo Sun; Li Cao (PLoS ONE)
Influenza virus is the cause of significant morbidity and mortality, posing a serious health threat worldwide. Here, we evaluated the antiviral activities of Cryptoporus volvatus extract on influenza virus infection. Our results demonstrated that the Cryptoporus volvatus extract inhibited different influenza virus strain replication in MDCK cells. Time course analysis indicated that the extract exerted its inhibition at earlier and late stages in the replication cycle of influenza virus. Subsequently, we confirmed that the extract suppressed virus internalization into and released from cells. Moreover, the extract significantly reduced H1N1/09 influenza virus load in lungs and dramatically decreased lung lesions in mice. And most importantly, the extract protected mice from lethal challenge with H1N1/09 influenza virus. Our results suggest that the Cryptoporus volvatus extract could be a potential candidate for the development of a new anti-influenza virus therapy.